Knowledge and Attitude of Iranian University Students toward Genital Warts - Aryanian, Zeinab; Mohammadi, Maedeh; Babazadeh, Arefeh; Hatami, Parvaneh; Mohseni Afshar, Zeinab; Goodarzi, Azadeh; Etesami, Ifa; Barary, Mohammad; Ebrahimpour, Soheil; Sabbagh, Parisa (Interdisciplinary Perspectives on Infectious Diseases, 2022)
Human papillomavirus (HPV) is one of the well-known causes of cervical cancer and one of the most prevalent sexually transmitted diseases (STDs). Since cervical cancer is one of the most common causes of morbidity and mortality in women, this study was performed to investigate Iranian medical students’ knowledge and attitudes towards genital warts. This cross-sectional study assessed the perception and attitudes of 385 students at Babol University of Medical Sciences using a preconceived questionnaire. The participants’ mean age was 23.70 ± 3.27 years, with a range of 20–50 years. Evaluation of these students’ level of general information about HPV showed that 7 (1.8%) students had inadequate general information, 34 (8.8%) had moderate knowledge, and 344 (89.4%) had good general knowledge in this regard. There was also a significant association between students’ general knowledge of HPV and their field of study. Based on our results, the knowledge of the majority of Babol University of Medical Sciences students about genital warts was in a good range, and their knowledge about HPV routes of transmission was of moderate level. Moreover, the majority had an appropriate attitude to interact with people infected with HPV.